A catch-all discrete distribution: Short description and main properties - Nuno Fachada; João P. Matos-Carvalho; Carlos M. Fernandes (Examples and Counterexamples)
Consider a population of size N where each element has an independent probability p of being a success. By sampling this population without replacement, how many elements need to be drawn to find all successes? This paper describes this discrete distribution, derives its main properties, and validates the results through simulation.